Can a Trained Radiology Technician Do Arterial Obstruction Quantification in Patients With Acute Pulmonary Embolism? - Rotzinger, David C.; Breault, Stéphane; Knebel, Jean-François; Beigelman-Aubry, Catherine; Jouannic, Anne-Marie; Qanadli, Salah D. (Frontiers in Cardiovascular Medicine, 2019)
Objectives To assess interobserver variability between a trained radiology technician (RT) and an experienced radiologist in arterial obstruction quantification using the Qanadli obstruction index (QOI), in patients diagnosed with acute pulmonary embolism (APE) at CT pulmonary angiography (CTPA). Materials and Methods A RT and a radiologist independently reviewed CTPAs of 97 consecutive, prospectively enrolled patients with APE, and calculated the QOI. They classified patients into three risk categories: high for QOI ≥40%, intermediate for QOI 20-37.5%, low for QOI <20%. Interobserver variability was investigated for QOI as a continuous variable and as a categorical variable (high, intermediate, and low-risk groups). Results Mean QOI (±SD) was 39.5±24.3% and 38.6±18.9% for the RT and the radiologist, respectively. The mean QOI was not statistically different between the RT and the radiologist (p=0.502), and the interobserver agreement was excellent (ICC=0.905). The RT classified 54 patients (55.7%) as high, 17 (17.53%) as intermediate, and 26 (26.8%) as low risk. The radiologist classified 55 patients (56.7%) as high, 22 (22.7%) as intermediate, and 20 (20.6%) as low risk. The interrater agreement for risk stratification was excellent (weighted kappa=0.844). Conclusion Once the diagnosis of APE was established, an adequately trained RT achieved an accuracy comparable to that of an experienced radiologist regarding QOI calculation and risk assessment.